Strategi Guru Pendidikan Islam dalam Menginternalisasi Nilai Islam Melalui Permainan Edukatif di Tadika Al-Fikh Orchard - Nadia Dwi Haryuni; Hasrian Rudi Setiawan (Sekolah Tinggi Ilmu Tarbiyah Al-Bukhary Labuhanbatu, 2025)
This study is motivated by the need for Islamic character formation in early childhood through hidden curriculum amid modern moral challenges. The objective is to describe Islamic teachers’ strategies in internalizing Islamic values through educational games at Tadika Al-Fikh Orchard. The research employed a descriptive qualitative approach using field study methods. The population included teachers, a principal, and students at Tadika Al-Fikh Orchard Klang, Malaysia, with a purposive sample of three teachers, one principal, and six children aged 4-6 years. Main instruments were participatory observation sheets, semi-structured interviews, and documentation. Data were analyzed using Miles and Huberman’s model and NVivo thematic analysis. Findings reveal teachers’ strategies comprised exemplification, habituation through games, and reflective dialogues to internalize Islamic values, generating positive responses from students and parents. The conclusion confirms educational games as an effective medium for internalizing Islamic values, highlighting the crucial role of teachers as facilitators and role models, with recommendations for method innovation and enhanced parental involvement.